The Validity of QR-Code Digital Signature in Contract Towards The Evidence Agenda In Civil Court - Andriati, Syarifah Lisa; Aprilia Batubara, Dinda (Universitas Sumatera Utara, 2024)
This study delves into the validity of QR-Code Digital Signatures in contractual agreements within the framework of positive law in Indonesia, specifically examining their significance in the evidence agenda of Civil Courts. The objective is to assess the legal provisions surrounding QR-Code Digital Signatures and their potential role as substantial evidence in legal proceedings. By investigating the positive law perspective in Indonesia, the study aims to provide insights for legal practitioners and the public, emphasizing the strategic utilization of QR-Code Digital Signatures to enhance the authenticity of contracts and their admissibility as evidence in Civil Courts. Through this comprehensive exploration, the study aspires to offer a nuanced understanding of the legal standing of QR-Code Digital Signatures, providing valuable insights that contribute to the ongoing dialogue on the intersection of technology and law in the Indonesian context. This research uses normative juridical methods. The result of this research is the QR-Code Digital Signature in the contract is declared valid in positive law in Indonesia. Contracts with QR-Code Digital Signatures can be used as evidence if they meet the requirements in article 11 of the UU ITE. The existence of contracts with QR-Code Digital Signature as valid evidence in court still requires evidentiary arrangements in formal civil law to systematically regulate the process of proof in court so cannot violate the principle of openness of evidence at trial.